If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = 2p Solving -1 = 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -1 + -2p = 2p + -2p Combine like terms: 2p + -2p = 0 -1 + -2p = 0 Add '1' to each side of the equation. -1 + 1 + -2p = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2p = 0 + 1 -2p = 0 + 1 Combine like terms: 0 + 1 = 1 -2p = 1 Divide each side by '-2'. p = -0.5 Simplifying p = -0.5
| 4n-12-7n=6-2n-9 | | 2A+3B=2C | | 8(x+2)+5=45 | | 2n-12=8n+4 | | 14x+6y=0 | | 0.8x-0.9(18-4x)=-0.7(x-6) | | 64=2t^2-8 | | 8=6y-5y+4 | | 2x+9=7x+4x | | 7d+13=35-4b | | 21=y-(-6) | | 7x-x-1=11 | | -p+6p=6+2p | | -5(1-6r)=30-5r | | 0=t-12+3 | | 14-v=16 | | (7q+3)(4q+1)=0 | | 7x+6y=-14 | | 2m=3(m-10) | | 4(y-2)=29 | | 20-z=1 | | 7=7y+2 | | 9-4x=2+6 | | 5(x-2)+2(X+2)=10-2X | | r+3+12=-1 | | 20-2=1 | | 4x+1+2x+6x-10=180 | | 5n-4n+n-2=20 | | 14=0.1x+7 | | 4x-3(y-2)=15ty | | -4/1= | | 6w-1=8w+7 |